2004
DOI: 10.1139/f04-156
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of ontogenetic diet transitions in summer flounder (Paralichthys dentatus), using stable isotopes as diet tracers

Abstract: We examined the rate of isotopic change of nitrogen (N) and carbon (C) and isotopic fractionation at two temperatures during several ontogenetic diet transitions in summer flounder (Paralichthys dentatus). We examined prefeeding larvae as they metabolize the maternal source of nutrition and evaluated three diet transitions in the early life stages of this species: (i) yolk dependency to first feeding on zooplankton, (ii) one zooplankton (rotifers) to another (Artemia), and (iii) zooplanktivory to piscivory. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 22 publications
2
42
1
1
Order By: Relevance
“…Heady and Moore (2013) revealed that catabolism contributed more to 15 N turnover in tissues with faster turnover rates, contributing 68% for fin compared to 0.7% for scales. Experimental design, especially the temperature used, can also significantly impact turnover rates, with higher water temperatures reducing the half-lives of the carbon stable isotope of muscle in similar sized fish (Bosley et al, 2002;Witting et al, 2004). Caution must also be applied when the contributions of metabolism to turnover are estimated and represented by a metabolic constant, as this constant covers all non-growth processes that contribute to turnover, including inter-tissue recycling of nutrients, preferential isotopic routing and amino-acid effects, and these processes may operate differently during isotopic uptake and elimination (MacNeil et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heady and Moore (2013) revealed that catabolism contributed more to 15 N turnover in tissues with faster turnover rates, contributing 68% for fin compared to 0.7% for scales. Experimental design, especially the temperature used, can also significantly impact turnover rates, with higher water temperatures reducing the half-lives of the carbon stable isotope of muscle in similar sized fish (Bosley et al, 2002;Witting et al, 2004). Caution must also be applied when the contributions of metabolism to turnover are estimated and represented by a metabolic constant, as this constant covers all non-growth processes that contribute to turnover, including inter-tissue recycling of nutrients, preferential isotopic routing and amino-acid effects, and these processes may operate differently during isotopic uptake and elimination (MacNeil et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the half-lives estimated with this growth-based model were expressed as an x-fold mass increase. The fractions of new tissue derived from growth (D g ) and from metabolism (D m ) were calculated at the midpoint between the old and new isotopic values (Witting et al, 2004):…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, turnover rates can be well predicted by a time-based model. Relative to the time-based model, the growth-based model may be more suitable in experimental conditions of variable temperatures and growth rates because any variability in growth rates is inherently accounted for by the relative growth variable W R (Witting et al 2004). Bosley et al (2002) showed that c did not vary greatly between temperature treatments despite changes in fish growth rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the comparatively slow turnover observed in the fish muscle of juveniles < 30% L max (Hesslein et al 1993, Sweeting et al 2005) and the fact that turnover decelerates rapidly with age as reduction in growth-based dilution diminishes (Witting et al 2004), such variation is unlikely to strongly influence analysis of fish at 55 to 80% L max .…”
Section: Species Isotopic Analysesmentioning
confidence: 99%